PENGARUH JENIS SEDIAAN TOPIKAL EKSTRAK GONAD LANDAK LAUT (Diadema setosum) SEBAGAI PENYEMBUH LUKA BAKAR PADA KELINCI (Oryctolagus cuniculus) - Karmilah, Karmilah; Badia, Esti (Window of Health : Jurnal Kesehatan, 2019)
Burns is a form of tissue damage or loss caused by contact with heat sources such as fire, hot water, chemicals, electricity, and radiation. Sea urchin gonads contain high protein compounds, flavonoids, triterpenoids, steroids, saponins, and alkaloids that can prevent infection, anti-inflammatory, and help regenerate new cells. The purpose of this study was to determine whether the differences in the dosage form of topical preparations of sea urchin gonad 4% gave effect to the healing of burns based on wound healing up to 100%. The materials used in this study were ointments, creams, and gels containing 4% gonad sea urchin extract, ethyl chloride, alcohol. This study used an experimental method consisting of 8 treatment groups, namely 3 treatment groups prepared ointments, creams, and gels, 3 groups of preparations without extract (placebo), and 2 control groups. Each group is repeated three times (replication treatment). Descriptive results, preparations of ointments, creams, and gels provide healing effects of burns up to 100% for 27-30 days. The Kolmogorov-Smirnov statistical test results obtained p values> 0.05 (0.2) which means that data is normally distributed. The ANOVA test results p <0.05 (0.000) showed that all treatments gave significantly different effects. Based on the BNT test, it shows 4% of sea urchin gonad extract made in the form of ointment is more effective in healing burns.